"Rural mothers' feelings of isolation when caring for a child chronic health condition: A phenomenological study". (June 2022) - Bristow, Sally M.; Jackson, Debra; Power, Tamara; Usher, Kim
Evidence indicates that people in rural settings may experience difficulties in accessing health services, mainly specialist services. Caring for a child with a chronic health condition in a rural environment can present these mothers' challenges. This article reports one of four finding themes from a more extensive qualitative study on rural mothers' experiences of providing care for a child with a chronic health condition. Using hermeneutic phenomenological methods, narrative accounts were collected from 17 rural mothers of children with a chronic health condition in 2018. Analysis revealed that these mothers experienced emotional and physical isolation resulting in an overall theme reported within this article: " Alone in the Outback " : isolation, capturing rural mother's feelings of isolation; comprising three subthemes: On the fringe ; There is no shelter; and Choosing their own direction . Their experiences of caring highlighted a need for additional local carer support services and resources. Nurses can assist in supporting rural mothers through facilitating local social support networks enabling women to connect with others in similar caregiving situations. This study reports following the consolidated criteria for reporting qualitative research guidelines (Tong et al., 2007 ).